Constructing multi-enzymatic cascade reactions for selective production of 6-bromoindirubin from tryptophan in Escherichia coli - Lee, Jeongchan; Kim, Joonwon; Kim, Hyun; Park, Hyun A.; Kim, Jin Young; Kim, Eun Jung; Yang, Yung Hun; Choi, Kwon Young; Kim, Byung Gee (Biotechnology and Bioengineering, 2022)
6-Bromoindirubin (6BrIR), found in Murex sea snails, is a precursor of indirubin-derivatives anticancer drugs. However, its synthesis remains limited due to uncharacterized biosynthetic pathways and difficulties in site-specific bromination and oxidation at the indole ring. Here, we present an efficient 6BrIR production strategy in Escherichia coli by using four enzymes, that is, tryptophan 6-halogenase fused with flavin reductase Fre (Fre-L3-SttH), tryptophanase (TnaA), toluene 4-monooxygenase (PmT4MO), and flavin-containing monooxygenase (MaFMO). Although most indole oxygenases preferentially oxygenate the electronically active C3 position of indole, PmT4MO was newly characterized to perform C2 oxygenation of 6-bromoindole with 45% yield to produce 6-bromo-2-oxindole. In addition, 6BrIR was selectively generated without indigo and indirubin byproducts by controlling the reducing power of cysteine and oxygen supply during the MaFMO reaction. These approaches led to 34.1 mg/L 6BrIR productions, making it possible to produce the critical precursor of the anticancer drugs only from natural ingredients such as tryptophan, NaBr, and oxygen.
Keywords: 6-bromoindirubin; Anticancer drug; Cascade reactions; Flavin containing monooxygenase; Halogenase; Indigoids; Indirubin; Monooxygenases; Regiospecificity; Whole-cell biotransformations; Escherichia coli; Indoles; Oxygen; Tryptophan; 6-bromoindirubin; halogenase; indigoids; monooxygenase; regiospecificity; whole-cell biotransformation